PENERAPAN SISTEM TIGA STRATA (STS) UNTUK MENGATASI MASALAH HIJAUAN MAKANAN TERNAK PADA PETANI TERNAK SAPI DI DESA PENGOTAN, KABUPATEN BANGLI - I. B. Gaga Partama; D.P. M.A. Candrawati; I. W. Sudiastra; N. N. Candraasih Kusumawati; I. G. N. Kayana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2013)
This community service was conducted in a livestock groups of Bali cattle, one of the livestock groups is locatedat Pengotan village. Their members are peoples of Pengotan village, Bangli Regency. They are mostly farmers whoare still having productive farm lands with very limited extensions. Nowadays, along with the care for their cattle,they usually give their cattle green forage from natural grasses. Usually, the farmers offered the cattle by ricestraws from their waste of rice harvest which is plentiful enough along the year. They are only do it if they are indifficulties of getting enough fresh natural forages. Due to this condition, therefore socialization and demonstrationhow to place of planting high forages feedstuff (leguminoseae and nonleguminoseae) by Three Forages StratumSystem (STS) for planting high quality of forages and practice of biofermentation technology for increasing the ricestraw which helps to raise digestion for the livestocks. With this community service program, the expected resultis the members of group have knowledge and comprehension that rice straw could be used as source of forageswhich could be stored within 3 to 4 months with a Microorganisms culture (EM-4) fermentation method. Fromthis program, the participants have got appropriate knowledge to increase 90% about Three Forages StratumSystem (STS) for planting high quality forages and leguminoseae threes. It is concluded that by using both thefermented rice straw and plantation of high quality of forages by Three Forages Stratum System (STS) the farmerwould not be in difficulties to obtain green forages sources for their cattle.